Letter - Bell, Ernest A.
038-0004-001 26.9.49. Miss Cobbett I intended to raise this matter before the I.C. I recollect, however, that Mr Tewson had some correspondence with Lady Layton, the outcome of which I'm not clear about. It maybe, therefore, that Mr Tewson would prefer not to bring the matter before the Cttee, but to [deal] reply to the Union on the lines of his correspondence with L.L. EAB 292/946/38/4